Indirect maternal effects via nest microbiome composition drive gut colonization in altricial chicks - Diez-Méndez, David; Bodawatta, Kasun H; Freiberga, Inga; Klečková, Irena; Jønsson, Knud A; Poulsen, Michael; Sam, Katerina (Molecular ecology, 2023)
Gut microbial communities are complex and heterogeneous and play critical roles for animal hosts. Early-life disruptions to microbiome establishment can negatively impact host fitness and development. However, the consequences of such early-life disruptions remain unknown in wild birds. To help fill this gap, we investigated the effect of continuous early-life gut microbiome disruptions on the establishment and development of gut communities in wild Great tit (Parus major) and Blue tit (Cyanistes caeruleus) nestlings by applying antibiotics and probiotics. Treatment neither affected nestling growth nor their gut microbiome composition. Independent of treatment, nestling gut microbiomes of both species grouped by brood, which shared the highest numbers of bacterial taxa with both nest environment and their mother. Although fathers showed different gut communities than their nestlings and nests, they still contributed to structuring chick microbiomes. Lastly, we observed that the distance between nests increased inter-brood microbiome dissimilarity, but only in Great tits, indicating that species-specific foraging behaviour and/or microhabitat influence gut microbiomes. Overall, the strong maternal effect, driven by continuous recolonization from the nest environment and vertical transfer of microbes during feeding, appears to provide resilience towards early-life disruptions in nestling gut microbiomes.
Keywords: probiotics; Songbirds; mikrobiota; Microbiota; Animals; Maternal Inheritance; střevní mikroflóra; kur domácí; zpěvní ptáci; vertical transmission; brood feeding; maternální dědičnost; Passeriformes; Gastrointestinal Microbiome; zvířata; Chickens; antibiotics; environmental microbiomes